Are trade credits a gain or a drain? Power in the sale of feed to pangasius and tilapia farmers in Bangladesh. Issue 3 (2nd July 2020) - Islam, Imranul; Nielsen, Max; Ehlers, Birgit Schulze; Zaman, Badiuz; Theilade, Ida
Abstract: Trade credits provide financing to buyers who might not, otherwise, be able to operate a business. However, sellers may use trade credits to exploit market power and this introduces a market failure that reduces efficiency and social welfare when compared to a competitive market. The objective of this study is to investigate the costs of trade credits for fish feed to fish farmers in Bangladesh and shed light on the power relation as perceived by the farmers and feed sellers. The sources of power are determined by factor analysis. A one-way analysis of variance is used to identify the most powerful party. The results indicate that trade credits were more expensive than cash payments and even bank loans for farmers. The excess costs of trade credits indicate that feed sellers exploit their power and the identification of feed sellers as the powerful party supports this indication. Trade credits, therefore, provide gains in financing fish production that may not otherwise take place, but their costs decrease efficiency. Policymakers can increase efficiency by implementing corrective measures such as ceilings on the costs of trade credits; however, the remuneration of risk must be allowed for trade credits to prevail.